EFISIENKAH BANK UMUM SYARIAH DI INDONESIA? - Deny Dwi Hartomo; Dewi Endang Wijayanti (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2018)
The aim of this study is to measure the efficiency of Islamic Bank in Indonesia and to analyze the factors that affect the level of efficiency. The objects of this study are 12 (twelve) Islamic Bank in Indonesia which analyze from 2011 until 2015. The are 2 (two) methods which are used in this study, namely non-parametric method of Data Envelopment Analysis (DEA) on the first stage and Tobit model on the second stage. Overall, the result, show that the efficiency level of Islamic Bank in Indonesia during the time period in this study, not all of the Bank, have reach the optimum level of efficiency. There are a few of Islamic Bank that have not yet reach the optimum level of efficiency. Beside of the analysis from Tobit model show that Bank Size has a positive relation with Pure Technical Efficiency (PTE) and Bank Size has a negative relation with Scale Efficiency (SE).